Design and Construction of Tools for Fertilizing Palawija Plants - Asrul Baroqah, Mohd; Azriadi, Emon; Adeswastoto, Hanantatur (Journal of Engineering Science and Technology Management (JES-TM), 2024)
Corn (Zea mays L.) is one of the important food crops widely cultivated in various parts of the world, including Indonesia. This plant has high economic value and serves as a source of food, animal feed, and industrial raw materials. This research aims to design and create a corn fertilizer tool utilizing easily obtainable materials such as pipes, used buckets, and hoses. This fertilizer tool is designed using SolidWorks 2020 software to ensure precise and functional design. In the testing process, this tool was evaluated to measure the accuracy and efficiency of fertilizer distribution. The tank on this tool has a capacity of 10 kg, which is sufficient to meet the fertilization needs with a dosage of 300 kg per hectare. With a corn plant population of 71,000 plants per hectare, each corn plant requires about 4 grams of NPK fertilizer. The tool testing was conducted in Salo Timur Village, and the results showed that this tool can effectively and efficiently distribute fertilizer according to the needs of each corn plant.